2009
DOI: 10.1111/j.1467-7652.2009.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic chloroplasts are efficient sites for high‐yield production of the vaccinia virus envelope protein A27L in plant cells†

Abstract: SummaryOrthopoxviruses (OPVs) have recently received increasing attention because of their potential use in bioterrorism and the occurrence of zoonotic OPV outbreaks, highlighting the need for the development of safe and cost-effective vaccines against smallpox and related viruses. In this respect, the production of subunit protein-based vaccines in transgenic plants is an attractive approach. For this purpose, the A27L immunogenic protein of vaccinia virus was expressed in tobacco using stable transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Approximately the same level of VACV A27L protein production was achieved previously in plants transformed through the nuclear genome 24 .…”
Section: Synthesis and Accumulation Of A27l Protein In Transgenic Tobmentioning
confidence: 49%
“…Approximately the same level of VACV A27L protein production was achieved previously in plants transformed through the nuclear genome 24 .…”
Section: Synthesis and Accumulation Of A27l Protein In Transgenic Tobmentioning
confidence: 49%
“…In agreement with the observed phenotype, analysis by immunofluorescence microscopy performed on protoplasts isolated from transformed or wild-type plants showed altered chlorophyll distribution. 23 Moreover, transmission electron microscopy (TEM) analyses of leaf tissues indicated an alteration of chloroplast membrane ultrastructure in transplastomic plants (Fig. 2).…”
Section: Protein Accumulationmentioning
confidence: 98%
“…3,[23][24][25] For example, we expressed in transplastomic tobacco plants the immunogenic proteins A27L of vaccinia virus that accumulated to about 18% of total soluble protein. 23 We observed that in transplastomic lines the accumulation of the Rubisco large and small subunits was reduced. In soil, transplastomic plants grew more slowly and were chlorotic.…”
Section: Protein Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Major advantages of plant-made pharmaceuticals include low cost of production, higher scale-up capacity and lack of risk of contamination with mammalian pathogens. Several antigenic proteins have been produced in plant, examples are plant-made vaccines against smallpox, HIV and HPV (Human Papilloma Virus) (Lenzi et al, 2008;Rigano et al, 2009;Scotti et al, 2009). In addition, transgenic plants can represent a suitable vehicle for oral delivery of pharmaceuticals since the plant cell wall protects the recombinant antigen in the harsh condition of stomach and intestine (Sharma et al, 2008a).…”
Section: Production Of Pharmaceutical Proteinsmentioning
confidence: 99%